2011
DOI: 10.1007/s00417-011-1660-6
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic orbital tumors in southern China during an 18-year period

Abstract: The most common primary cancer that metastasizes to the orbit is nasopharyngeal carcinoma (30.34%), followed by lung cancer (8.70%) and liver cancer (6.52%) in southern China. Orbital metastasis can display a variety of clinical features and should be considered in patients with known systemic cancer. The systemic prognosis is generally poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…An Italian study, performed on 93 patients, found the greatest percentage of mammary origin (36%), followed by kidney (10%), lung (8%) and skin (6%) (14). Another study, carried out in Southern China on 46 patients, showed a higher percentage of nasopharyngeal origin (30%), followed by lung (8%), liver (6%), kidney (4%) and breast (4%) (15). Finally, a Japanese study, performed on 128 patients, found the greatest frequency of pulmonary origin (16%), followed by breast (15%), liver (14%), adrenal neuroblastoma (7%) and kidney (3%) (16).…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study, performed on 93 patients, found the greatest percentage of mammary origin (36%), followed by kidney (10%), lung (8%) and skin (6%) (14). Another study, carried out in Southern China on 46 patients, showed a higher percentage of nasopharyngeal origin (30%), followed by lung (8%), liver (6%), kidney (4%) and breast (4%) (15). Finally, a Japanese study, performed on 128 patients, found the greatest frequency of pulmonary origin (16%), followed by breast (15%), liver (14%), adrenal neuroblastoma (7%) and kidney (3%) (16).…”
Section: Discussionmentioning
confidence: 99%
“…As our case showed, a contrast-enhanced CT of the orbit or MRI establishes the diagnosis of orbital involvement. Metastasis appears as a high-density soft tissue mass of the involved orbit with a marked contrast enhancement 15. However, this imaging finding is non-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for orbital metastasis is generally palliative. Systemic corticoids and chemotherapy can be used 7 15. But, orbital radiotherapy is the mainstay therapy and can improve orbital symptoms in 70–90% of cases and diminish the size of the tumour 16.…”
Section: Discussionmentioning
confidence: 99%
“…In southern China, the most common primary cancer that metastasizes to the orbit is nasopharyngeal carcinoma (30.34%), followed by lung cancer and liver cancer [5]. There is no exact information about the most common type of NPC in Syria.…”
Section: Discussionmentioning
confidence: 99%